1977
DOI: 10.1073/pnas.74.10.4595
|View full text |Cite
|
Sign up to set email alerts
|

Differential lateral mobility of IgM and IgG receptors in mouse B lymphocyte membranes

Abstract: Anti-Ig induced redistribution of different Ig subclasses was studied as a function of temperature and correlated with membrane phase transitions as revealed by electron spin resonance spectroscopy. Fluorescein isothiocyanate-coupled anti-IgG2 and anti-IgM antibodies induced patching and capping that proceeded with increasing rates from 20 to 40 (measured at 20 intervals). Characteristic temperatures marked the onset of discontinuities in such rate changes. IgG2-bearing lymphocytes displayed discontinuities at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Preliminary studies using 12NS-GA and mouse B lymphocytes (specifically, IgG2 bearing cells) revealed only two characteristic temperatures at approximately 14 and 28 °C. Lymphocytes spin labeled with 5N10 displayed the usual four characteristic temperatures (Krolick et al, 1977). These preliminary results suggest that 12NS-GA is a potentially valuable membrane surface probe for intact cells.…”
Section: Discussionmentioning
confidence: 70%
“…Preliminary studies using 12NS-GA and mouse B lymphocytes (specifically, IgG2 bearing cells) revealed only two characteristic temperatures at approximately 14 and 28 °C. Lymphocytes spin labeled with 5N10 displayed the usual four characteristic temperatures (Krolick et al, 1977). These preliminary results suggest that 12NS-GA is a potentially valuable membrane surface probe for intact cells.…”
Section: Discussionmentioning
confidence: 70%
“…We predict that the bi-loop structure ( Supplementary Figure S1 ) instead of a stem–loop region in TD05 melts with increasing temperature, yielding a low-affinity structure B at physiological temperatures that cannot compete with the thermal instability, resulting in dissociation of the complex. Moreover, it has been reported that, the lateral angle of the mIgM in the membrane changes with temperature due to changes of the hydrocarbon structure of the membrane of B lymphocytes ( 37 ). As the nature of the aptamer–epitope interaction is nonlinear, the aforementioned changes in both aptamer and the membrane of the lymphocytic cells with temperature might negatively affect the complex, leading to dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…These differences between cell spreading on α‐IgM and α‐CD44 may be due to changes in cell stiffness. This is supported by a report in which B‐lymphocytes treated with α‐IgM displayed increased membrane rigidity, driving the recovery of membrane tension [Krolick et al, ; Pasternak and Elson, ]. The absence of defects seen in cell spreading induced via α‐IgM can be explained by the compensatory role played by other class I myosins (such as Myo1c and Myo1e that are also expressed in B‐cells) [Maravillas‐Montero et al, ].…”
Section: Discussionmentioning
confidence: 62%